Remobilized dust dynamics and inventory evolution in ITER-like start-up plasmas. (1st January 2023) - Vignitchouk, L; Paschalidis, K; Ratynskaia, S; Tolias, P; Pitts, R A
Abstract: The dynamics of remobilized metallic dust are simulated with the MIGRAINe code in low-power ITER discharges meant to emulate reactor start-up environments. The particle size and speed distributions are varied along with plasma profiles to investigate the influence of initial and background parameters on high- Z impurity production by vaporization as well as long-term in-vessel dust inventory evolution over the course of consecutive discharges. Simulation output data regarding beryllium remobilization can be integrated into more global ITER models to guide the operation of dust diagnostics and facilitate the compliance with nuclear safety restrictions, while results on tungsten particles serve as a basis for first assessments of dust dynamics in DEMO.